Fire on the Prairie : Harold Washington, Chicago Politics, and the Roots of the Obama Presidency. - Rivlin, Gary (Urban life, landscape, and policy., 2012)
Harold Washington's historic and improbable victory over the vaunted Chicago political machine shook up American politics. The election of the enigmatic yet engaging Washington led to his serving five tumultuous years as the city's first black mayor. He fashioned an uneasy but potent multiracial coalition that today still stands as a model for political change.In this revised edition of Fire on the Prairie, acclaimed reporter Gary Rivlin chronicles Washington's legacy-a tale rich in character and intrigue. He reveals the cronyism of Daley's government and Washington's rivalry wi.